Measurement and properties of the dose-area product ratio in external small-beam radiotherapy - Niemelä Jarkko; Partanen Mari; Ojala Jarkko; Sipilä Petri; Björkqvist Mikko; Kapanen Mika; Keyriläinen Jani (IOP PUBLISHING LTD, 2022)
In small-beam radiation therapy (RT) the measurement of the beam quality parameter, i.e. the tissue-phantom ratio or TPR20,(10), using a conventional point detector is a challenge. To obtain reliable results, one has to consider potential sources of error, including volume averaging and adjustment of the point detector into the narrow beam. To overcome these challenges, a different type of beam quality parameter in small beams was studied, namely the dose-area product ratio, or DAPR(20),(10). With this method, the measurement of a dose-area product (DAP) using a large-area plane-parallel chamber (LAC) eliminates the uncertainties in detector positioning and volume averaging that are present when using a point detector. In this study, the properties of the DAPR(20),(10) of a cone-collimated 6 MV photon beam were investigated using Monte Carlo (MC) calculations and the obtained values were compared to measurements obtained using two LAC detectors, PTW Type 34073 and PTW Type 34070. In addition, the possibility of determining the DAP using EBT3 film and a Razor diode detector was studied. The determination of the DAPR(20),(10) value was found to be feasible in external small-beam radiotherapy using cone-collimated beams with diameters from 4-40 mm, based on the results of the two LACs, the MC calculations and the Razor diode. The measurements indicated a constant DAPR(20),(10) value for fields 20-40 mm in diameter, with a maximum relative change of 0.6%, but an increase of 7.0% for fields from 20-4 mm in diameter for the PTW Type 34070 chamber. Simulations and measurements showed an increase of DAPR(20),(10) with increasing LAC size or dose integral area for the studied 4-40 mm cone-collimated 6 MV photon beams. This has the consequence that there should be a reference to the size of the used LAC active area or the DAP integration area with the reported DAPR(20),(10) value.